GIS-Based Landslide Disaster Risk Areas and Ground Movements Mapping to Support Disaster Mitigation Activities (Case Study: Tasikmalaya Regency) - Novi Asniar; Anri Noor Annisa Ramadan; Aso Sudiarjo (LPPM Universitas Ma Chung, 2021)
Tasikmalaya Regency is an area that is prone to landslides and ground movements. The availability of comprehensive and accurate information in controlling land use for regional development in areas prone to landslides and ground movements is very important for casualty prevention and other losses such as physical, social and economic. This information must be disseminated to the public as an early warning system to support disaster mitigation efforts. Identification of the characteristics of landslide and ground movement prone areas requires the mapping of risk areas to mitigate disasters. This can be done using Geographic Information System (GIS). This mapping activity was carried out using the method of collecting digital data from five vulnerability controlling factors of landslides and ground movements, namely rainfall, rock type, soil type, land cover and slope. The analysis is continued by weighting the factors that influence landslides and ground motion and then overlaying the five controlling factor maps (with their respective weight values) to produce a landslides and ground movement vulnerability level map which is then inputted into WebGIS. This map can then be used by local governments and the public as an information medium to support disaster mitigation activities.